UPAYA MINIMASI WASTE PADA PROSES PENGADAAN BARANG/JASA DI PT PERTAMINA HULU ENERGI (PHE) MENGGUNAKAN LEAN SERVICE - Bobby Cahyo Widiantoro (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. The purpose of this research is to identify and reduce waste in theprocurement process of goods/services at PT Pertamina Hulu Energi (PHE). Theprocurement process analysis of good/services uses the concept of lean thinkingthat begins with the observation that focused on process of good/servicesprocurement. Based on the current state mapping, there was several wastes at theinitial inquiry stage or good/services procurement process which incomplete, arecurring assessment process in the pre-qualification stage of goods/servicesprocurement, and the long contract process. Future state mapping showed theimprovement process by applying the procedure of goods/services procurementinquiry, making the certified to replace administration document, and applying theGeneral Terms and Conditions of the contract. Total cycle time to responseincomplete request showed the significance improvement from 3.600 seconds to 0second. Total cycle time for prequalification process showed significantimprovement from 345.600 seconds to 3.600 seconds or improve 98,96%. Totalcycle time for contract process showed the significant improvement from1.209.600 seconds to 432.000 seconds or improve 64,29%. Based on thecalculation of process cycle efficiency value showed the significant improvementfrom 0,58 to 0,83 or improve 30%.Keywords: procurement process, lean services, process cycle efficiency.